Role of protein S deficiency in children with venous thromboembolism - Klostermeier, Ulrich C.; Limperger, Verena; Kenet, Gili; Kurnik, Karin; Gelas, Martine Alhenc; Finckh, Ulrich; Junker, Ralf; Heller, Christine; Zieger, Barbara; Knöfler, Ralf; Holzhauer, Susanne; Mesters, Rolf; Krümpel, Anne; Nowak-Göttl, Ulrike (Thrombosis and Haemostasis, 2015)
Venous thromboembolism [TE] is a multifactorial disease, and protein S deficiency [PSD] constitutes a major risk factor. In the present study the prevalence of PSD and the clinical presentation at TE onset in a cohort of children is reported. In 367 unselected paediatric patients with TE (age 0.1–18 years) recruited between July 1996 and December 2013, a comprehensive thrombophilia screening was performed along with recording of anamnestic data. Thirty of 367 paediatric patients (8.2 %) derived from 27 families had PSD. Mean age at first TE onset was 14.5 years (range 0.1 to 18). Thrombotic locations were cerebral veins (n=8), calf vein TE (n=3) deep veins (DVT) of the leg (n=12), DVT & pulmonary embolism (n=5) and intra-cardiac veins (n=1) or purpura fulminans (n=1). PSD co-occurred with the factor 5 mutation at rs6025 or the homozygous factor 2 susceptibility variant at rs1799963 in one case each. The Heerlen polymorphism detected in five children presented with milder PSD. In 18 patients (60 %) a concomitant risk factor for TE was identified. A second TE event within primarily healthy siblings occurred in three of 27 PSD families (11.0 %). In this cohort of children with symptomatic TE, the prevalence of PSD adjusted for family status was 7.4 %. Given its clinical implication for patients and family members, thrombophilia testing should be performed and the benefit of medical or educational interventions should be evaluated in this high-risk population.
Keywords: Protein S deficiency; genetics; children